50 Years A Slave: A Review on Philippine Labour Migration - Fonte, Allain (Advances in Social Sciences Research Journal, 2021)
pstrongAbstract/strong/ppstrongnbsp;/strong/ppThe Philippines has been deploying migrant workers to more than 192 countries, with a rising number that exceeds up to a million workers every year.nbsp;nbsp; In 2009, the record of migrant workers’ remittances went up to 17.4 billion US dollars from 10.4 billion US dollars in 2005.nbsp; Reports showed that remittances comprise a bigger portion of the Philippines’ gross domestic product, as it contributed 10.8% to the GDP in 2005, and 11.1% in 2009.nbsp; After more than 50 years of deploying Filipino workers overseas, the Philippines should have improved with its labour policies and implementing them.nbsp; Yet, reports on abuses of Filipino workers can still be read and heard.nbsp;/ppThis paper reviews the two most controversial cases where the Philippine government had failed to protect its migrant workers by analysing its then labour policies; and how they have impacted the labour and migration sectors to ensure the welfare of its migrant workers.nbsp; Further, this research discusses reoccurring issues such as delayed services from government agencies, lack of administrative skills to process complaints and cases of Filipino migrant workers, poor communication and coordination among government offices, labour policies that do not abide by the constitution, and the unfair provisions in the treaties between Philippines and destination countries for low-skilled workers./ppnbsp;/ppstrongKeywords/strong emlabour migration, migration, migrant workers, labour policies/em/p